Assessing Creativity in Early Primary Education: Insights from the Merdeka Curriculum in Indonesian Language Learning - Tia Athifah; Rizal Rizal; Muhammad Aqil; Pahriadi Pahriadi; Putriwanti Putriwanti; Surahman Wilade (Papanda Publisher, 2026)
This study examined the effect of the Merdeka Curriculum on creativity development among second-grade students in Indonesian language learning at SD Negeri 02 Dolo. Despite growing emphasis on 21st-century competencies, traditional teacher-centered instruction continues to dominate Indonesian primary classrooms, potentially constraining creativity development. A quasi-experimental one-group pretest-posttest design was employed, complemented by classroom observations, questionnaires, and interviews with 30 second-grade students and their teacher. Data were analyzed using paired-samples t-tests, descriptive statistics, and thematic analysis. Results revealed a paradoxical pattern: while standardized creativity test scores showed minimal change (p = 0.012, d = 0.15), substantial improvements emerged in creative behaviors, autonomous learning, and student engagement. Classroom observation ratings progressed from 80% to 100%, and qualitative data documented increased idea generation, willingness to experiment, and confidence in creative expression. These findings suggest that student-centered, project-based curricula foster meaningful creativity development in young learners, manifesting primarily through behavioral processes rather than immediate test performance gains. The study contributes to early primary education scholarship by revealing limitations of traditional written assessments for capturing children's creativity and supporting the need for multimodal, process-oriented evaluation approaches. Results carry implications for curriculum implementation, teacher professional development, and creativity assessment practices in early primary contexts.